Development of Organic Medicine Plants as Solutions for Improving The Economy and Health in Penatih Village During COVID-19 - Anak Agung Putu Agung Mediastari; Ni Luh Gede Sudaryati; Anak Agung Komang Suardana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The COVID-19 pandemic has caused many social problems, especially the decline in the quality of health due to the lack of people's sources of income. The cultivation of organic medicinal plants in the community is a solution to improve the degree of health and help the community's economic recovery. The community does not have the understanding and ability to cultivate organic medicinal plants and use them as medicine and a source of income. This program aims to promote understanding, capability, and implementation of methods for cultivating organic medicinal plants, post-harvest processing, and their use as medicine and generate household-level economic value. The mentoring process lasted for six months in Penatih Village. Assistance is carried out by providing understanding, knowledge, and practice in developing organic medicinal plants through workshops and assisting the governance of land use, cultivation results, and their use for medicine and economic value. Evaluation of the community's knowledge, understanding, and skills is carried out through post-program interviews. The assistance results show that the community feels the impact of the organic medicinal plant seeds provided. Planting organic herbal medical plants and generating herbal medicinal raw materials with high economic value, such as empon- empon (rhizomes), to raise people's family income increases their knowledge, understanding, and abilities of land management governance. This activity is meant to be long-lasting so that the Organic Herbal Medicine Tourism Village can be built in Penatih Village and help the area's economy.